(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2018)
The main objective of this study is to determine the level of effect of play in the child’s development along physical, cognitive and socio-emotional development of the respondents who are enrolled in pre-kindergarten at Capitol Church Nursery - Kindergarten, which served as a basis for the formulation of an Instructional Material for enhancement activities. The research was carried out during the 1st semester of school year 2015-2016. There were 40 respondents from the pre-kindergarten of Capitol Church Nursery and Kindergarten. It was administered by the teachers, the student teachers and the parents, guardians. The researchers used the descriptive correlation research design. The results obtained reveal that the CCNK pre-kindergarten pupils along the different indicators are in advance development. Significant relationship only exists between the birth order and the socio-emotional development, while the rest of the variables have no significant relationship. It is then concluded that there is an advanced development in the level of effect of play along physical, cognitive and socio-emotional development. Based on the research findings and conclusions, the researchers prepared an instructional material which incorporates enhanced activities involving play in the development of the child.